Subthreshold Autism Spectrum in a Patient with Anorexia Nervosa and Behçet's Syndrome. (15th June 2020) - Dell'Osso, L.; Carpita, B.; Cremone, I. M.; Mucci, F.; Salerni, A.; Marazziti, D.; Carmassi, C.; Gesi, C.
Abstract : Recently, increasing research stressed the presence of subthreshold autistic traits in patients with other psychiatric conditions. In this framework, a significant relationship between anorexia nervosa (AN) and the autism spectrum has been frequently reported, in particular among female samples, to the point that AN has been hypothesized to be a female phenotype of autism spectrum disorder (ASD). On the other hand, among subjects with ASD has been reported a higher prevalence of immune diseases and altered immune functions. While these reports seem to support an association between neurodevelopmental and immune system alterations in ASD, the relationship between the immune system and the broader autism spectrum, including its subthreshold manifestations, remains poorly investigated. In this report, we described the presence of autistic traits in a male inpatient with AN and separation anxiety disorder, who also show a diagnosis of Behçet's syndrome (BS). This case seems to further stress the association between AN and the autism spectrum, which may not be limited to the female gender. Moreover, it further suggests a deeper link between neurodevelopmental and immune system alterations. Implications are discussed in light of the more recent neurobiological and psychopathological hypothesis about the autism spectrum.